Implementation Open Source System Resource Planning In Sustainable Supply Chain Management of Small and Medium Enterprise - Agung Terminanto; Achmad Nizar Hidayanto; Fajar Budi Utomo (International Journal of Supply Chain Management, 2020)
Abstract— In the production logistics context, the success of supply chains corresponds to their ability to meet the logistic performance expectations of customers. This ability depends on the contributions of all supply chain members to the logistical performance of the entire chain. Implementation of ERP system is one way that can be done to improve the performance of company. Implementation of ERP System using open source with ASAP method. Open source selected is Odoo. Use case modeling is used to design and describe user permissions. Created gap analysis and flow map of purchase orders process, incoming product and outbound input to compare business process before and after using Odoo. Implementation is initiated by restore master data activity. Furthermore, setting the Odoo on the Warehouse and Purchase module. After the implementation of Odoo in PT SJM, the existing documents can be accessed in real-time and increased efficiency of activity in the Warehouse, the amount of activity by 31%, the number of documents reduced by 50%, the efficiency traveled by 91% which is 48% faster, and all data is integrated into one database. This indicates that Odoo provides benefits for improving company performance.